Fucoxanthin has potential for therapeutic efficacy in neurodegenerative disorders by acting on multiple targets. (3rd October 2022) - Yang, Mengxiang; Xuan, Zhenquan; Wang, Qiyao; Yan, Sicheng; Zhou, Dongsheng; Naman, C. Benjamin; Zhang, Jinrong; He, Shan; Yan, Xiaojun; Cui, Wei
ABSTRACT: Fucoxanthin, one of the most abundant carotenoids from edible brown seaweeds, for years has been used as a bioactive dietary supplement and functional food ingredient. Recently, fucoxanthin was reported to penetrate the blood–brain barrier, and was superior to other carotenoids to exert anti-neurodegenerative disorder effects via acting on multiple targets, including amyloid protein aggregation, oxidative stress, neuroinflammation, neuronal loss, neurotransmission dysregulation and gut microbiota disorder. However, the concentration of fucoxanthin required for in vivo neuroprotective effects is somewhat high, and the poor bioavailability of this molecule might prevent its clinical use. As such, new strategies have been introduced to overcome these obstacles, and may help to develop fucoxanthin as a novel lead for neurodegenerative disorders. Moreover, it has been shown that some metabolites of fucoxanthin may produce potent in vivo neuroprotective effects. Altogether, these studies suggest the possibility for future development of fucoxanthin as a one-compound-multiple-target or pro-drug type pharmaceutical or nutraceutical treatment for neurodegenerative disorders. Trial registration: ClinicalTrials.gov identifier: NCT03625284 . Trial registration: ClinicalTrials.gov identifier: NCT02875392 . Trial registration: ClinicalTrials.gov identifier: NCT03613740 . Trial registration: ClinicalTrials.gov identifier: NCT04761406 .